A 65-Year-Old Male with Primary Central Nervous System Diffuse Large B-Cell Lymphoma on Nivolumab with Oral Mucositis and Targetoid Plaques - Severine Cao; Pooyan Rohani; Rosalynn M. Nazarian; Daniela Kroshinsky (MDPI AG, 2017)
Background/Aims: The development of programmed cell death-1 (PD-1) inhibitors has greatly improved patient outcomes in the treatment of a variety of advanced malignancies. These novel immunotherapies are not without adverse effects, the most common of which are dermatologic. Methods: We report our experience with an atypical erythema multiforme-like eruption in a patient with primary central nervous system diffuse large B-cell lymphoma treated with nivolumab. Results: The patient presented with oral mucositis and scattered erythematous papules which progressed to targetoid purpuric plaques with hyperkeratotic centers. Histopathology demonstrated interface dermatitis with dyskeratotic keratinocytes and pigment incontinence. The patient experienced improvement of the eruption with discontinuation of nivolumab and on systemic and topical glucocorticoids. Conclusion: As PD-1 inhibitors become more widely used in the treatment of advanced malignancies, the early recognition and treatment of rare dermatologic toxicities remain of great importance.